Spontaneous ventral urethral fistula whose mother had a retained IUD in uterus during the gestation - Wei, Shuyi; Li, Qiang; Li, Senkai; Zhou, Chuande; Li, Fengyong (Canadian Urological Association Journal, 2014)
Urethral fistula is rare and is usually a complication of penile and urethral surgery. A few congenital cases have been reported. To our knowledge, there are only 2 reports about spontaneous ventral urethral fistula in the English literature. We present what we believe is the first case of a patient with spontaneous ventral urethral fistula whose mother had a retained IUD in uterus during the gestation.